An overview of Teletalk’s market position compared to the other Telecommunication industries of Bangladesh - Khan, Md. Ashfaq Ullah (Brac University, 2020)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2020.